Phytic acid attenuates acetaminophen-induced hepatotoxicity via modulating iron-mediated oxidative stress and SIRT-1 expression in mice - Hassan, Hend M.; Abdel-Halim, Nehal H. M.; El-Shenbaby, Ibrahim; Helmy, Manar A.; Hammad, Maha O.; Habotta, Ola A.; El Nashar, Eman M.; Alghamdi, Mansour A.; Aldahhan, Rashid A.; Al-Khater, Khulood M.; Almohaywi, Basmah; Farrag, Eman A. E. (Frontiers in Pharmacology, 2024)
Introduction: Administration of high doses of acetaminophen (APAP) results in liver injury. Oxidative stress and iron overload play roles in the pathogenesis of APAP-induced hepatotoxicity. The present study assessed the potential hepatoprotective effects of phytic acid (PA), a natural antioxidant and iron chelator, on APAP-induced hepatotoxicity and the possible underlying mechanism through its effects on CYP2E1 gene expression, iron homeostasis, oxidative stress, and SIRT-1 expression levels. Methods: Twenty-four adult male albino mice were used in this study. Mice were divided into four groups (six mice in each group): control, APAP-treated, PA-treated and APAP + PA-treated groups. Liver function tests, serum and liver tissue iron load were evaluated in all the study groups. Hepatic tissue homogenates were used to detect oxidative stress markers, including malondialdehyde (MDA) and reduced glutathione (GSH). Histological hepatic evaluation and immunohistochemistry of SIRT-1 were performed. Quantitative real-time PCR was used for the assessment of CYP2E1 and SIRT-1 gene expressions. APAP-induced biochemical and structural hepatic changes were reported. Results: PA administration showed beneficial effects on APAP-induced hepatotoxicity through improvements in liver functions, decreased CYP2E1 gene expression, decreased serum and liver iron load, decreased MDA, increased GSH, increased SIRT-1 expression level and improvement in hepatic architecture. Conclusion: Conclusively, PA can be considered a potential compound that can attenuate acetaminophen-induced hepatotoxicity through its role as an iron chelator and antioxidant, as well as the up-regulation of SIRT-1 and down-regulation of CYP2E1.